Osteoblastic Differentiation of Human Adipose-Derived Mesenchymal Stem Cells on P3HT Thin Polymer Film - Paola Campione; Maria Giovanna Rizzo; Luana Vittoria Bauso; Ileana Ielo; Grazia Maria Lucia Messina; Giovanna Calabrese (Journal of Functional Biomaterials)
Bone defects restoration has always been an arduous challenge in the orthopedic field due to the limitations of conventional grafts. Bone tissue engineering offers an alternative approach by using biomimetic materials, stem cells, and growth factors that are able to improve the regeneration of bone tissue. Different biomaterials have attracted great interest in BTE applications, including the poly(3-hexylthiofene) (P3HT) conductive polymer, whose primary advantage is its capability to provide a native extracellular matrix-like environment. Based on this evidence, in this study, we evaluated the biological response of human adipose-derived mesenchymal stem cells cultured on P3HT thin polymer film for 14 days. Our results suggest that P3HT represents a good substrate to induce osteogenic differentiation of osteoprogenitor cells, even in the absence of specific inductive growth factors, thus representing a promising strategy for bone regenerative medicine. Therefore, the system provided may offer an innovative platform for next-generation biocompatible materials for regenerative medicine.